To write the equation in standard form and solve for q, we need to gather all like terms on one side of the equation:
4q^2 + 3q = 3q^2 - 4q + 18
Rearranging the terms:
4q^2 + 3q - 3q^2 + 4q = 18
Simplifying:
q^2 + 7q = 18
Rearranging the terms into standard form:
q^2 + 7q - 18 = 0
Now, we can factor the quadratic equation:
(q + 9)(q - 2) = 0
Setting each factor to zero and solving for q:
q + 9 = 0
q = -9
q - 2 = 0
q = 2
Therefore, the solutions to the equation q^2 + 7q - 18 = 0 are q = -9 or q = 2.
Write the equation in standard form. Then solve.
4q^2+3q=3q^2-4q+18
(1 point)
q=2 or 9
q=0 or 18
q=-9 or 2
q=-7 or 3
1 answer